Post‐anaesthetic emergence delirium in adults: incidence, predictors and consequences. Issue 8 (10th March 2016) - Munk, L.; Andersen, G.; Møller, A. M.
Abstract : Background: Emergence delirium (ED) after general anaesthesia (GA) is a well‐known phenomenon, yet the risk factors are still unclear. The aims of this study were to determine the incidence and independent predictors of ED and secondly to determine to which degree ED has any relevant, clinical consequences to medical staff as well as to patients. Method: This prospective, observational cohort study assessed adult patients emerging from GA in the operating room, using the Richmond Agitation–Sedation Scale (RASS). Signs of ED, defined as RASS≥1 along with possible clinical consequences were noted. Patients with ED were re‐evaluated in the post‐anaesthesia care unit (PACU) and concomitant patient and anaesthesia related factors were noted. Results: Among the 1970 patients enrolled, 73 (3.7%) showed signs of ED when emerging from anaesthesia. When reassessed in PACU, the number had declined to 25 patients (1.3%). Male sex, endotracheal tube (ETT) and volatile anaesthetics were found to be significantly related to developing ED after anaesthesia. In 20 cases, additional staff had to be called for and in one case, an i.v. access was accidentally removed. Neither patients nor staff were hurt. Conclusion: Male sex, volatile anaesthetics and ETT were factors significantly related to ED. Whether gender, choice of respiratory devices and anaesthetics are true predictors or derived factors of surgery procedures, duration of surgery and the patients' physical condition need further investigation. The most notable clinical consequence of ED was the need of additional staff in order to restrain the agitated patient.